2017
DOI: 10.1016/j.physbeh.2017.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Fluid, energy and nutrient recovery via ad libitum intake of different fluids and food

Abstract: Introduction: This study compared the effects of ad libitum consumption of different beverages and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 34 publications
(31 reference statements)
1
25
0
Order By: Relevance
“…Nevertheless, athletes quite often finish exercise in fluid deficit (Sawka et al, 2007), which has resulted in considerable interest in understanding factors influencing fluid recovery (Maughan, Leiper, & Shirreffs, 1997;Shirreffs, Armstrong, & Cheuvront, 2004;Shirreffs & Maughan, 2000;Campagnolo et al, 2017). As our research has revealed, 31.6% of men influencing one or more of the factors that limit exercise performance (Maughan, 2001).…”
Section: Resultsmentioning
confidence: 81%
“…Nevertheless, athletes quite often finish exercise in fluid deficit (Sawka et al, 2007), which has resulted in considerable interest in understanding factors influencing fluid recovery (Maughan, Leiper, & Shirreffs, 1997;Shirreffs, Armstrong, & Cheuvront, 2004;Shirreffs & Maughan, 2000;Campagnolo et al, 2017). As our research has revealed, 31.6% of men influencing one or more of the factors that limit exercise performance (Maughan, 2001).…”
Section: Resultsmentioning
confidence: 81%
“…Specifically, the administration of a CHO-electrolyte sports beverage increased energy (M: ~2.5 MJ, or ~32%; F: ~1.0 MJ, or ~25%) and CHO (M: ~186 g, or ~95%; F: ~73 g, or ~68%) intake, compared to water. The milk-based formulations also increased energy and nutrient provision (to a similar extent observed with the CHO-electrolyte sports beverage for males and to an even greater extent in females); though, these tended to increase ratings of gastrointestinal (GI) discomfort [16][17][18]. Given that in both previous investigations participants were free to leave the laboratory at the end of the recovery period, the extent to which anticipation of a subsequent exercise session influences food/fluid choices requires clarification.…”
Section: Introductionmentioning
confidence: 82%
“…Two recent studies conducted in our laboratory have investigated how the provision of different beverages influences post-exercise fluid/nutrient recovery when consumed voluntarily and with access to food [16,17].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations